2009
DOI: 10.2109/jcersj2.117.221
|View full text |Cite
|
Sign up to set email alerts
|

Calcite mesocrystals: a very effective block polyelectrolyte for crystal "Morphing"

Abstract: A family of calcite nanocrystal superstructures with unusual morphology were obtained from crystallization of calcite by the CO2 gas diffusion technique in the presence of a bioinspired double hydrophilic block copolymer, polyethyleneglycol-blockpoly (L-aspartic acid). From the typical calcite rhombohedra as a starting situation, the morphology can be systematically varied via various unusual porous mesocrystal morphologies to hemispheres composed of fine calcite triangles. The formation of mesocrystals is sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Figure 5, right). [54] The most surprising fact was the unexpected high potency of the additive. Already at concentration in the ppm range, efficient change of the nucleation mechanism was found, turning a ''regular'' default calcite crystal into a mesocrystal with surface roughness and developed texture.…”
Section: Programming Interactions Toward Crystallization Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5, right). [54] The most surprising fact was the unexpected high potency of the additive. Already at concentration in the ppm range, efficient change of the nucleation mechanism was found, turning a ''regular'' default calcite crystal into a mesocrystal with surface roughness and developed texture.…”
Section: Programming Interactions Toward Crystallization Processesmentioning
confidence: 99%
“…Already at concentration in the ppm range, efficient change of the nucleation mechanism was found, turning a ''regular'' default calcite crystal into a mesocrystal with surface roughness and developed texture. [54] Depending on the polymer/mineral ratio, very specific structural features were discovered due to the multiple roles of the polymer additives involved in crystallization processes. In most cases a surprising and unexpected beauty of the as formed structures was revealed.…”
Section: Programming Interactions Toward Crystallization Processesmentioning
confidence: 99%
“…The effects of polymers' additives on the crystallization kinetics and crystal morphology of CaCO 3 were also studied. For example, Colfen et al [26][27][28][29][30] studied the morphology changes of CaCO 3 crystals in the presence of block copolymers additives and it was shown that CaCO 3 crystallizes, resulting in the formation of CaCO 3 mesocrystals. The presence of carrageenan polysaccharides as additive in the crystallization of CaCO 3 and its various effects on the crystallization kinetics and crystal morphology will be discussed separately.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the interference of sulfonate group and the polymer backbone, ACC NPs are easily formed and in situ stabilized by PSS. Previously, Wang et al [49,50] have confirmed the existence of PSS-Ca 2+ complex in solution ahead of crystallization. They further demonstrated that the early nanoparticles are amorphous.…”
Section: Preparation and Characterizations Of Bowknot Caco 3 Particlesmentioning
confidence: 92%